Multi-Material Additive Manufacturing of Sustainable Innovative Materials and Structures - Singh, Rupinder (Polymers (Basel), 2019)
This paper highlights the multi-material additive manufacturing (AM) route for manufacturing of innovative materials and structures. Three different recycled thermoplastics, namely acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), and high impact polystyrene (HIPS) (with different Young’s modulus, glass transition temperature, rheological properties), have been selected (as a case study) for multi-material AM. The functional prototypes have been printed on fused deposition modelling (FDM) setup as tensile specimens (as per ASTM D638 type-IV standard) with different combinations of top, middle, and bottom layers (of ABS/PLA/HIPS), at different printing speed and infill percentage density. The specimens were subjected to thermal (glass transition temperature and heat capacity) and mechanical testing (peak load, peak strength, peak elongation, percentage elongation at peak, and Young’s modulus) to ascertain their suitability in load-bearing structures, and the fabrication of functional prototypes of mechanical meta-materials. The results have been supported by photomicrographs to observe the microstructure of the analyzed multi-materials.